1985
DOI: 10.1126/science.4048936
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Autoimmune Thyroiditis in Chickens by Dietary Iodine

Abstract: Clinical studies have suggested that excess dietary iodine promotes autoimmune thyroiditis; however, the lack of a suitable animal model has hampered investigation of the phenomenon. In this study, different amounts of potassium iodide were added to the diets of chicken strains known to be genetically susceptible to autoimmune thyroiditis. Administration of iodine during the first 10 weeks of life increased the incidence of the disease, as determined by histology and the measurement of autoantibodies to triiod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
70
3
2

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(77 citation statements)
references
References 15 publications
2
70
3
2
Order By: Relevance
“…Studies in both humans and animals have demonstrated that iodine administration may enhance autoimmune thyroiditis (4,5,(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). Totally, three mechanisms (47) have been assumed for the development of iodine-induced autoimmune thyroiditis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in both humans and animals have demonstrated that iodine administration may enhance autoimmune thyroiditis (4,5,(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). Totally, three mechanisms (47) have been assumed for the development of iodine-induced autoimmune thyroiditis.…”
Section: Discussionmentioning
confidence: 99%
“…ncreased iodine (I) ingestion has been shown to promote induction of autoimmune thyroiditis in humans (1-5) and experimental animals such as chicken (6,7), rats (8 -12), hamsters (13), and mice (14). The mechanisms underlying this association remain poorly understood.…”
mentioning
confidence: 99%
“…NOD.H-2h4 mice spontaneously develop SAT (1)(2)(3)(4)(5)(6). Increased dietary iodine accelerates development of SAT in NOD.H-2h4 mice (1-3), humans, obese strain (OS) chickens, and BB/Wor rats (23)(24)(25). Recent work showed that enhanced iodination of thyroglobulin facilitates processing and presentation of a cryptic pathogenic peptide and this might partly account for the association of high iodine intake and autoimmune thyroiditis (26).…”
mentioning
confidence: 99%